Mobile Banking Usability Evaluation among Deaf: A Review on Financial Technology and Digital Economy Prospects - Vija Kumaran, Vikniswari; Soosay Nathan, Shelena; Hussain, Azham; Hashim, Nor Laily (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This study is aimed to explore the dimensions for appropriate deaf people usability evaluation model for M-banking application in order to enhancetheir satisfaction. Through the systematic literature review (SLR) conducted, four dimensions (efficiency, effectiveness, satisfaction and accessibility) have been identified to be appropriate to suit the need of m-banking application usability evaluation especially for the deaf people. Furthermore, innovation and technologies through digital economy are practical and aptly accessible to allows persons who are deaf to fully participate in society, education, and business while also providing prospects for personal and professional advancement. Moreover, this study will be able to provide recommendation to the upper management of Malaysia Banks to concern on mobile services in order to enhance the deaf customers’ satisfaction. Financial and economy implications together with future research suggestions are also discussed in this study.